WLE/ICRAF soil spectral technology impacting soil restoration strategies and investments are being scaled up from Africa to global use - CGIAR Research Program on Water, Land and Ecosystems (2019)
WLE/ICRAF’s soil spectroscopy initiatives have moved from African outcomes to achieving global outcomes. Growing donor interest in deploying low-cost soil spectral technology in agricultural projects for better evidence-based investments is leading to major investments in India, Haiti, and elsewhere. WLE and the Food and Agriculture Organization-led Global Soil Laboratory Network are leading a new initiative to develop a free global soil mid-infrared spectral library and prediction service in collaboration with the Kellogg Soil Survey Laboratory in the United States.